New method to prepare W-B+-N ternary barrier to Cu diffusion by implanting BF2+ ions into W-N thin film - Kim, DJ; Kim, YT; Park, JW (A V S AMER INST PHYSICS, 1999)
Implanting 1 x 10(17) BF2+ ions/cm(2) with as low an energy as 40 keV into W-N thin films, W-B+-N thin layer was formed fdr the region near the surface of the W-N thin film. Experimental results reveal that thermal stability of the W-B+-N/W-N thin film and its barrier performance against Cu diffusion were improved compared to these of the W-N thin films after annealing at 600-800 degrees C for 30 min. These excellent properties of the W-B+-N/W-N barrier are due to the B+ ions to prevent nitrogen out-diffusion and to keep the W-B+-N/W-N thin film in an amorphous phase after annealing at 800 degrees C because the grain growth of W or W-N and the Cu diffusion were suppressed by the B and N impurities in the amorphous thin film. (C) 1999 American Vacuum Society. [S0734-211X(99)02204-0].
Keywords: THERMAL-STABILITY; TUNGSTEN; METALLIZATION